Immunohistochemical study on the PCNA-immunoreactivity in the uterus of rats ovariectomized or treated with antiestrogen clomiphene citrate - Canpolat, Leyla; Özercan, İbrahim Hanifi; Bozlak, Nurten; Doğan, Cengiz (My University, 1999)
PCNA (proliferating cell nuclear antigen) immunoreactivity in the uterus of mature rats was investigated after long term administration of clomiphene citrate and ovariectomy. In the luminal epithelium and glandular epithelium and endometrial stroma regions, few PCNA-immunoreactive cells were observed. PCNA reactivity was estimated for the luminal and glandular epithelium and for the stromal cells. Treatment of clomiphene citrate decreased the proliferation of the luminal epithelial cell and stromal cells to the same extent as ovariectomy. In both of these groups, the proportion of anti-PCNA positive cells in the glandular epithelium was significantly higher than in the luminal epihelium and stromal cells. Clomiphene citrate has a strong antiproliferative effect on the uterus of rats, and this antiestrogenic action is specific for cell types.
Keywords: Uterus; Rats; Immunohistochemistry; Estrogen Antagonists; Clomiphene; Proliferating Cell Nuclear Antigen